Effect of haematological alterations on thalassaemia investigation in HIV-1-infected Thai patients receiving antiretroviral therapy - Sakorn Pornprasert (2018)
Objectives: To evaluate the effect of haematological alterations resulting from antiretroviral therapy (ART) on the diagnosis of thalassaemia carriers in HIV-1-infected Thai patients. Methods: Complete blood cell counts, osmotic fragility (OF) test and haemoglobin (Hb)-A2 values were measured in blood samples of 52 antiretroviral-treated and 14 untreated HIV-1-infected patients. Data were analysed according to thalassaemia type and ART. Results: Sixteen patients carried at least one of the investigated thalassaemia types and most of them (87.5%) received ART. Their red cell indices [mean corpuscular Hb (MCH), mean corpuscular Hb concentration (MCHC) and red blood cell distribution width (RDW)], OF test and Hb-A2 values were observed within the critical criteria of each thalassaemia type. Normocytic red cells were observed in α-thalassaemia and Hb-E trait. Among HIV-1-infected patients who are non-thalassaemia carriers, higher values of Hb-A2, MCH, macrocytosis and lower red cell counts were observed in the treated group. Values of RDW, MCHC and OF test for treated and untreated groups were in the normal range. Five treated patients had Hb-A2 values within the critical criteria of β-thalassaemia carriers but β-thalassaemia gene mutations were not observed by polymerase chain reaction analysis. Conclusions: ART can alter many haematological figures. Therefore, diagnosis of thalassaemia should be evaluated carefully in combination with those parameters. © 2008 British HIV Association.